Recent Advances in Planar Optics-Based Glasses-Free 3D Displays - Hua, Jianyu; Qiao, Wen; Chen, Linsen (Frontiers in Nanotechnology, 2022)
Glasses-free three-dimensional (3D) displays are one of the technologies that will redefine human-computer interfaces. However, many geometric optics-based 3D displays suffer from a limited field of view (FOV), severe resolution degradation, and visual fatigue. Recently, planar optical elements (e.g., diffractive gratings, diffractive lenses and metasurfaces) have shown superior light manipulating capability in terms of light intensity, phase, and polarization. As a result, planar optics hold great promise to tackle the critical challenges for glasses-free 3D displays, especially for portable electronics and transparent display applications. In this review, the limitations of geometric optics-based glasses-free 3D displays are analyzed. The promising solutions offered by planar optics for glasses-free 3D displays are introduced in detail. As a specific application and an appealing feature, augmented reality (AR) 3D displays enabled by planar optics are comprehensively discussed. Fabrication technologies are important challenges that hinder the development of 3D displays. Therefore, multiple micro/nanofabrication methods used in 3D displays are highlighted. Finally, the current status, future direction and potential applications for glasses-free 3D displays and glasses-free AR 3D displays are summarized.